Acellular Porcine Corneal Stroma May Not Be Optimal for Peripheral Keratoplasty: Reports of 2 Cases. Issue 4 (19th April 2021) - Li, Saiqun; Xiao, Peng; Deng, Yuqing; Li, Meng; Wang, Qian; Yuan, Jin
Abstract : Purpose: Although acellular porcine corneal stroma (APCS) is a promising alternative to the human donor cornea for lamellar keratoplasty, here, we report 2 patients who exhibited persistent epithelial defects and sterile keratolysis after APCS transplantation to treat peripheral corneal diseases. Methods: Two patients with different peripheral corneal diseases underwent lamellar keratoplasty by using D-shaped lamellar APCS as graft materials. Standard keratoplasty postoperative treatments, including topical antibiotic-corticosteroid, tacrolimus, and artificial tears, were applied. Results: Patient 1 was a 7-year-old boy with limbal dermoid, and patient 2 was a 50-year-old man suffered from simultaneous Mooren ulcer with pterygium. Both patients developed persistent graft epithelial defects postoperatively, which were refractory to conventional nonsurgical therapies. The APCS grafts were noted to start sterile keratolysis at approximately 1 month after implantation and were completely dissolved within 3 months, leaving vascularized scars in the previously grafted area. Conclusions: These 2 cases demonstrated that given the high risk of postoperative persistent epithelial defect and sterile keratolysis, the application of APCS in peripheral keratoplasty may need further evaluation.